Collective efficacy, alcohol outlet density, and young men's alcohol use in rural South Africa. (July 2015) - Leslie, Hannah H.; Ahern, Jennifer; Pettifor, Audrey E.; Twine, Rhian; Kahn, Kathleen; Gómez-Olivé, F. Xavier; Lippman, Sheri A.
Abstract: Alcohol use contributes to morbidity and mortality in developing countries by increasing the risk of trauma and disease, including alcohol dependence. Limited research addresses determinants of alcohol use beyond the individual level in sub-Saharan Africa. We test the association of community collective efficacy and alcohol outlet density with young men's drinking in a cross-sectional, locally representative survey conducted in rural northeast South Africa. Informal social control and cohesion show protective associations with men's heavy drinking, while alcohol outlet density is associated with more potential problem drinking. These findings provide initial support for intervening at the community level to promote alcohol reduction. Highlights: We test social and structural factors as predictors of young men's alcohol use. Informal social control and cohesion are associated with reduced heavy drinking. Alcohol outlet density is associated with elevated potential problem drinking. Community factors may provide means to intervene on alcohol use and related harms.